Analysis of the Methodology of Fixed Assets in Accordance with IAS 16 “Fixed Assets” AND P(S)BU 7 “Fixed Assets”: Theory and Practice - L. V. Shkulipa (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The importance of transparent, complete, authentic and timely information comprehensible for all the users of financial reporting has grown in the context of Ukraine’s integration in the international economy. The issue of harmonizing the national accounting system with the international standards is, therefore, on the agenda of the national statistics system. Apart from this, introduction of the international accounting standards in the Ukrainian statistics practice is expected to make Ukraine more attractive for foreign investors and lenders. As theoretical and practical problems related with harmonizing the national accounting standards with international ones are not fully elaborated, the article’s purpose is to analyze the methodology of fixed assets recording by international and national standards, with providing, in table form, comparative characteristics of the underlying sections of International Accounting Standards (IAS) 16 and Rules (Standards) of Accounting (R(S)A) enforced in Ukraine, and to illustrate their practical use. The comparison covers recognition, valuation, recording and reporting of fixed assets, elements of the original cost (estimates at the date of recognition), formation of the original value of fixed assets as a result of various events, revaluation of fixed assets, frequency of revaluation of the liquidation value of fixed assets etc. Practical issues related with fixed assets overvaluation (undervaluation), depreciating, disposal and exchange are highlighted.   The comparative analysis shows quite significant differences between the two documents in valuation, revaluation, liquidation, disposal of fixed assets. They can be explained by national specifics of record keeping in Ukraine, fully considered in the national standards, and, consequently, by adaptation of accounting in Ukraine to the national economy needs.